The Case of the Missing Disciple: Abū l-Ḥasan al-Rustughfanī and the First Reception of al-Māturīdī’s Theology in Samarqand - Harvey, Ramon (Oriens, 2021)
Abstract Despite recognition of Abū l-Ḥasan al-Rustughfanī (d. ca. 345/956) as the most important student of Abū Manṣūr al-Māturīdī (d. 333/944), a sustained treatment of his theological views has not hitherto appeared. One of the challenges that has been identified in prior studies is a lack of primary sources. To overcome this obstacle, I analyse manuscripts of “Bāb al-mutafarriqāt min fawāʾid” and “al-Asʾila wa-l-ajwiba,” two texts recording al-Rustughfanī’s theological responsa, locating them within available bibliographic information and discussing the question of literary structure. I then contextualise the material within the polemical milieu of mid-fourth/tenth century Samarqand, arguing that al-Rustughfanī is the earliest figure in the Samarqandī Ḥanafī kalām tradition to self-consciously adopt the full name ahl al-sunna wa-l-jamāʿa to express his theological identity. Finally, I provide an annotated theological overview of the main doctrines found in the texts with a detailed case study on divine speech and the Qurʾān, showing how al-Rustughfanī bridges the gap between al-Māturīdī’s rationalistic kalām and the Ḥanafī traditionalism of al-Ḥakīm al-Samarqandī (d. 342/953).